Investment innovation trends: Factor-based investing - Centineo, Sanja; Centineo, Santo (Serbian Journal of Management, 2017)
This article shows that it can take a long period of time until research knowledge finds its application in practice and get disseminated as innovation trend. Factor-based investing is such an example. Having its developing roots in the nineties, it took more than two decades until this approach was detected by the by investment community. The goal of this article is to recall the definition of factor investing, present its historical evolvement and motivate its recent break-through and current trend among investment practitioners (known also under the notion smart beta). It aims at familiarizing with this investment approach from a practical perspective and highlighting its diversifying benefits in a portfolio context with the potential to outperform the market on risk-adjusted basis.